Crafting careers through theory-driven interventions: a scoping review of the utility of social cognitive career theory and career maturity inventory - Pooja Damodar; Ankitha Shetty; Melanie Pius Dsouza; Arjun Prakash; Nachiket Gudi (International Journal of Adolescence and Youth, 2024)
In the intricate tapestry of the exploration stage (14–25 years), students grapple with the challenges of self-discovery, career ambiguity, and the quest for purpose. Over the last few decades, a vast body of research evidence on the utility of ‘Social Cognitive Career Theory’ (SCCT) and ‘Career Maturity Inventory’ (CMI) in designing career interventions has emerged. This framework and instrument can potentially assist students in navigating the critical exploration stage. As espoused by Arksey and O’Malley, our scoping review outlines the utility of SCCT and CMI in designing early career intervention. In addition, we identify and document the facilitators and barriers to utilizing SCCT and CMI. It presents the nuanced application of the framework and the instrument in rural and urban settings. The findings affirm the robust utility of SCCT and CMI, thereby informing academicians and practitioners in designing and implementing effective early career interventions.